Pengaruh Perbandingan Komposisi Pembiayaan Bagi Hasil, Murabahah, dan Ijarah Terhadap Kinerja Lembaga keuangan Syariah - Setyasih, Riztina Dwi (Fakultas Ekonomi dan Bisnis Islam (FEBI), Institut Agama Islam Negeri (IAIN) Purwokerto, 2020)
The tittle of this research is the effect of Yield financing composition, Murabahah, and Ijarah towards Sharia financial institutions performance. The purpose of this research is to test the effect of the composition of financing for the outcome, Murabahah, and Ijarah on the performance of sharia Bank and sharia business Unit. Financial performance is viewed based on Return On Asset (ROA) percentages. This research is a quantitative study using secondary data. The population in this study amounted to 14 for sharia banks and 20 Sharia business units. Sampling techniques in this study using purposive sampling so that the samples obtained as many as 8 Sharia banks and 6 Sharia business units. The period of research is quarterly for a period of 2 years so that the total amount of data is 64 sharia Bank and 48 Syariah business units. The data analysis technique used is a double linear regression analysis. The results of this test showed that a variable of financing composition for the outcome significantly negative impact on the financial performance of Sharia General Bank (BUS). The composition of murabahah financing has a significant positive impact on the financial performance of Syariah General Bank (BUS). The composition of financing Ijarah has a significant positive impact on the financial performance of Syariah General Bank (BUS). The composition of financing for the results has a significant positive impact on the financial performance of Syariah business units (UUS). The composition of murabahah financing has significant positive impact on the financial performance of Sharia Business Unit (UUS). The composition of financing Ijarah has significant negative impact on the financial performance of Syariah business Unit (UUS). And the composition of Sharia Business Unit financing is better than Sharia Commercial Banks